Pengaruh Latihan Beban Menggunakan Bench Press terhadap Daya Ledak Otot Lengan Atlet Karate - Fella Maifitri (Universitas Putra Indonesia YPTK Padang, 2018)
The problem in this study was the low ability of the muscle explosive power of the UK Karate UNP athletes. This study aims to see the effect of weight training using Bench Press on the explosive power of arm muscles of UK karate athletes at UNP. The population in this study were athletes from the Padang State University Karate Activity Unit, amounting to 15 people. Sampling is done by Total Sampling, then the sample in this study amounted to 15 people. The treatment in this study was carried out as many as 16 meetings and measurements of arm muscle explosive power before and after treatment (pretest-posttes design). The instrument used in this study was the Two Hand Medicine Ball Put test. After the data is obtained, the data is analyzed using t-test. The results showed: weight training using the Bench Press had a significant effect on the explosive power of the athlete's arm Unit of Karate University Padang State University's karate activity was proven where t count 6.42> t table 2.15 thus the hypothesis in this study was accepted.